MIRACLES-CURSES OF PAIN MANAGEMENT: A HUMBLE PLEA FOR CONSCIENTIOUS USE OF OPIOIDS - Gupta, Deepak (Indian Journal of Community Health, 2013)
Pain has been recognized as global public health concern [1] and inadequate pain management has been called public health crisis [2] with over six million people annually suffering across the world due to inaccessibility to controlled medications [3]. However, aggressively overcoming inadequacies in non-acute pain management has its costs too [4]; and societies that are at infantile stages in regards to managing these pains (chronic and cancer pains) in their patient population should not compare themselves with the fore-runners in pain management only in terms of per capita consumption of medicinal morphine equivalents [5] for pain relief.